Association between spicy food and hypertension among Han Chinese aged 30-79 years in Sichuan Basin: a population-based cross-sectional study - Liling Chen; Rui Ding; Qinwen Luo; Xiaojun Tang; Xianbin Ding; Xianxian Yang; Xiang Liu; Zhifeng Li; Jingru Xu; Jiantong Meng; Xufang Gao; Wenge Tang; et al. (BMC, 2023)
Abstract Background While spicy food is believed to have cardiovascular-protective effects, its impact on hypertension remains uncertain due to conflicting findings from previous studies. This study aimed to explore the association between spicy food and hypertension in Sichuan Basin, China. Methods The baseline data of 43,657 residents aged 30-79 in the Sichuan Basin were analyzed including a questionnaire survey (e.g., sociodemographics, diet and lifestyle, medical history), medical examinations (e.g., height, body weight, and blood pressure), and clinical laboratory tests (e.g., blood and urine specimens). Participants were recruited by multi-stage, stratified cluster sampling in consideration of both sex ratio and age ratio between June 2018 and February 2019. Multivariable logistic regression was performed to explore the effect of spicy food on hypertension and multivariable linear regression was applied to estimate the effect of spicy food on systolic and diastolic blood pressure (SBP/DBP). Results Concerning hypertension, negative associations with spicy food consumption were observed only in females: compared to those who do not eat spicy food, the odds ratios of consuming spicy food 6-7 days/week, consuming spicy food with strong strength, and years of eating spicy food-to-age ratio were 0.886 (0.799, 0.982), 0.757 (0.587, 0.977), 0.632 (0.505, 0.792), respectively. No significant association was found in males (All P trends > 0.05). In the stratified analyses, participants in the subgroup who were 50 to 79 years old (OR, 95%CI: 0.814, 0.763, 0.869), habitually snored (OR, 95%CI: 0.899, 0.829, 0.976), had a BMI < 24 kg/m2 (OR, 95%CI: 0.886, 0.810, 0.969), had a normal waist circumference (OR, 95%CI: 0.898, 0.810, 0.997), and had no dyslipidemia (OR, 95%CI: 0.897, 0.835, 0.964) showed a significantly stronger association. For SBP, consuming spicy food had negative effects in both genders, but the effect was smaller in males compared to females: among males, the β coefficients for consuming spicy food 1-2 days/week, weak strength, and years of eating spicy food-to-age ratio were 0.931 (-1.832, -0.030), -0.639 (-1.247, -0.032), and − 2.952 (-4.413, -1.492), respectively; among females, the β coefficients for consuming spicy food 3-5 days/week, 6-7 days/week, weak strength, moderate strength, and years of eating spicy food-to-age ratio were − 1.251 (-2.115, -0.388), -1.215 (-1.897, -0.534), -0.788 (-1.313, -0.263), -1.807 (-2.542, -1.072), and − 5.853 (-7.195, -4.512), respectively. For DBP, only a positive association between the years of eating spicy food-to-age ratio and DBP was found in males with β coefficient (95%CI ) of 1.300 (0.338, 2.263); Little association was found in females (all P trends > 0.05), except for a decrease of 0.591 mmHg ( 95%CI: -1.078, -0.105) in DBP among participants who consumed spicy food 1-2 days/week, compared to those who did not consume spicy food. Conclusion Spicy food may lower SBP and has an antihypertensive effect, particularly beneficial for women and individuals with fewer risk factors in the Sichuan Basin. Spicy food consumption may decrease DBP in women but increase it in men. Further multicenter prospective cohort studies are needed to confirm these findings.